Karakteristik Edible Film Komposit Pati Sagu Molat-Pektin [Characteristics of Edible Film from Composite of Molat Sago Starch-Pectin] - Febby J Polnaya; Natalia D. J. Alfons; Agustina Souripet (Pusat Penelitian dan Pengembangan Perkebunan, 2019)
The utilization of starch-base ingredients, such as sago starch for the manufacture of edible films, is still growing. The nature of the film produced from starch material is still not optimal, hence research is needed to improve its utilization. Starch composites with other ingredients, such as pectin, are expected to grow their properties. The study aimed to characterize the properties of edible film produced from molat sago starch-pectin composites, including thickness, tensile strength, elongation, solubility, transparency, and water vapor transmission rate. The study was conducted from July to August 2017 at Food Chemistry and Biochemistry Laboratory, Pattimura University, Ambon, and Food Engineering Laboratory, Gadjah Mada University, Yogyakarta. The design used was a non-factorial completely randomized design of the treatment of composite sago-pectin starch, with five levels of treatment (3: 0; 2.75:0.25; 2.5:0.5; 2.25:0.75 and 2:1 (g/g)). Based on the results of the analysis of diversity, the treatment of composite sago-pectin starch affects the changes in the mechanical, physical, and barrier characteristics of the edible film. Increasing the concentration of pectin (0-1%) in the film solution decreases the elongation of the film, but increases the properties of thickness, tensile strength, solubility, transparency, and the rate of water vapor transmission. The treatment of sago-pectin starch composites 2:1 can improve the physical and mechanical properties of edible films, although it has a high value of solubility and water vapor transmission rate.ABSTRAKPemanfaatan bahan dasar pati-patian, seperti pati sagu untuk pembuatan edible film masih terus berkembang. Sifat film yang dihasilkan dari bahan pati-patian masih belum optimal. Diperlukan penelitian untuk dapat meningkatkan pemanfaatannya. Komposit pati dengan bahan lainnya, seperti pektin diharapkan dapat meningkatkan sifat-sifatnya. Tujuan penelitian adalah mengkarakteristik sifat-sifat edible film yang dihasilkan dari komposit pati sagu molat-pektin, meliputi ketebalan, kuat tarik, elongasi, daya larut, transparansi dan laju transmisi uap air. Penelitian dilaksanakan pada bulan Juli sampai dengan Agustus 2017 di Laboratorium Kimia dan Biokimia Pangan, Universitas Pattimura, Ambon, dan Laboratorium Rekayasa Pangan, Universitas Gadjah Mada, Yogyakarta. Rancangan yang digunakan adalah Rancangan Acak Lengkap (RAL) dengan perlakuan adalah komposit pati sagu molat-pektin, dengan lima taraf perlakuan (3:0; 2,75:0,25; 2,5:0,5; 2,25:0,75 dan 2:1 (g/g)). Berdasarkan hasil analisis keragaman, perlakuan komposit pati sagu molat-pektin berpengaruh terhadap perubahan sifat-sifat mekanik, fisik dan barrier edible film. Meningkatnya konsentrasi pektin (0-1%) pada larutan film menurunkan elongasi film, tetapi meningkatkan sifat-sifat ketebalan, kuat tarik, daya larut, transparansi, dan laju transmisi uap airnya. Perlakuan komposit pati sagu molat-pektin 2:1 dapat memperbaiki sifat fisik dan mekanik edible film walaupun daya larut dan nilai laju transmisi uap airnya tinggi.